A Case of Buccal Clear Cell Carcinoma Caused by Rare Fusion Gene: EWSR1-CREM. (20th October 2021) - Hoshino, Miyako; Inoue, Katsuyuki; Kaneda, Tomohisa; Nishimura, Michiko; Kusama, Kaoru; Sakashita, Hideaki; Sato, Yukiko; Takeuchi, Kengo; Nagao, Toshitaka; Kikuchi, Kentaro
Abstract : Clear cell carcinoma (CCC) is a rare entity in the salivary gland tumor. So far, only 10 cases of primary CCC of the buccal mucosa have been reported. Here, we first report an extremely rare case of buccal CCC with the EWSR1-CREM fusion gene. The patient, a 69-year-old woman, presented with a painless mass in the right buccal mucosa. The tumor, which had been present for about 10 years, measured approximately 15 mm in diameter and was pedunculated, elastic hard, smooth, and mobile. Histopathological examination revealed proliferating tumor cells with vacuolated and clear cytoplasm partially surrounded by hyalinized stroma. The tumor was not encapsulated, and no contact with the overlying epithelium was evident. Duct-like structures were occasionally observed in the tumor nests composed of clear cells. The tumor had invaded into surrounding muscle and adipose tissues. Immunohistochemical examination revealed that the clear cells were positive for epithelial cell markers, and myoepithelial markers were negative. Fluorescence in situ hybridization (FISH), performed to search for genetic abnormalities, demonstrated split positivity for EWSR1, and fusion with CREM was confirmed. These findings suggested a diagnosis of CCC.